The relationship between motor coordination, executive functioning and attention in school aged children - Piek, Jan; Dyck, Murray; Nieman, Ally; Anderson, M.; Hay, David; Smith, Leigh; McCoy, M.; Hallmayer, J. (Elsevier, 2004)
Given the high level of comorbidity of attention deficit hyperactivity disorder (ADHD) and developmental coordination disorder (DCD), deficits in executive function (EF), shown to be present in children with ADHD, may also be implicated in the motor coordination deficits of children with DCD. The aim of this study was to explore the relationship between EF and motor ability. A sample of 238 children, 121 girls and 117 boys, aged between 6 and 15 years was recruited for this project. Motor ability was assessed using the McCarron Assessment of Neuromuscular Development (MAND), level of inattention using the Child Behavior Checklist (CBCL), and Verbal IQ (VIQ) was estimated using subtests of the WISC-III. A reaction time task and three EF tasks measuring response inhibition, working memory and the ability to plan and respond to goal-directed tasks were administered. It was found that motor ability significantly accounted for variance in tasks measuring speed of performance, whereas inattention appeared to influence performance variability. Despite past evidence linking poor motor ability with inattention, there was little overlap in the processes that are affected in children with motor coordination or attention problems.